2017
DOI: 10.1017/s1431927617008984
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of Ferroelectric Domain Walls and Crystallographic Defects in the PbTiO3 Films

Abstract: Both domain walls and lattice defects are known to have great influences on the properties of a ferroelectric, the detailed interactions between them and the resultant novel phenomena are still less known. In the tetragonal ferroelectrics, previous experimental investigations indicate that misfit dislocations form at film deposition temperature when PbTiO 3 (PTO) is cubic with a relatively larger lattice constant compared to SrTiO 3 (STO), while these dislocations may further promote the nucleation of a-domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It was shown that the coupling of the ferroelastic domain wall with point defects can lead to a giant electromechanical response 53 and atypical domain configurations including charged 90 o domain walls. 54 Therefore, the broadened domain wall observed here not only accommodates local strains and mobile point defects, but also could play a significant role in the electromechanical response.…”
Section: Resultsmentioning
confidence: 80%
“…It was shown that the coupling of the ferroelastic domain wall with point defects can lead to a giant electromechanical response 53 and atypical domain configurations including charged 90 o domain walls. 54 Therefore, the broadened domain wall observed here not only accommodates local strains and mobile point defects, but also could play a significant role in the electromechanical response.…”
Section: Resultsmentioning
confidence: 80%